Analisis Kepuasan Taruna Terhadap Fasilitas Perpustakaan Dalam Rangka Menyiapkan Sumber Daya Manusia Pada Era Society 5.0 - Rezki Fitra Ramadhan; Gagat Riano; Ismoyo Ismoyo (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The Indonesian Air Force Academy Library is a facility prepared by the Indonesian Air Force Academy whose task is to carry out support for the cadets and users in every activity at the Indonesian Air Force Academy. In this case, the AAU's library also requires attention, especially in terms of care and maintenance of the facilities in the AAU's library. To find out the cadet's satisfaction with the facilities in the AAU's library, it was done by distributing questionnaires to 36 respondents to find out the actual value and the expected value received by the cadets or SERVQUAL SCORE. The measurement of cadet's satisfaction is carried out on five dimensions, namely tangible, reliability, assurance, responsiveness, and empathy. From the measurement results, it is known that the 5 SERVQUAL dimension values ​​have an actual value of 6.7 and an expected value of 7.4 so that there is still a gap of -0.7 . From this gap, each attribute is grouped into four quadrants based on the priority of improvement using the IPA (Importance-Performance Analysis) diagram.